Isolation and Identification of Biosurfactantproducing Bacteria from the Aerobic Pond of Oil Palm Liquid Waste at PT. Aek Loba Plantation - Andini, Diah Ayu; Rasyidah, Rasyidah; Mayasari, Ulfayani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Biosurfactants are natural surfactants derived from bacteria which can degrade oil content in soil or water. Most of these biosurfactant-producing bacteria are often found in areas polluted by oil and grease, such as aerobic ponds of palm oil liquid waste. The purpose of this research was to isolate and identify biosurfactant-producing bacteria from aerobic ponds of palm oil wastewater at PT. Aek Loba Plantation. This research was conducted using descriptive and identification methods through emulsification tests, morphological characterization, gram staining, biochemical tests, and PCR (Polymerase Chain Reaction) methods for bacteria that had the highest emulsification index values. Based on the results of the emulsification test, it was found that 8 biosurfactant-producing bacterial isolates consisted of 6 bacterial genera and 1 bacterial species that had different emulsification indexes, namely 1 Citrobacter genus isolate (30%), 1 Enterobacter genus bacterial isolate (42.2%) , 2 isolates from the genus Eschericia (35.9% and 36.5%), 1 isolate from the genus Pseudomonas (32%), 1 isolate from the genus Micrococcus (37.5%), 1 isolate from the genus Bacillus, and 1 species of bacteria Klebsiella variicola (42.8%) which is a biosurfactant producing bacteria that has the highest emulsification index value.